PENGARUH FAKTOR ELECTRONIC WORD OF MOUTH (EWOM) DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN E-COMMERCE SHOPEE - Fakhira, Eko Riski; N, Arizal; Nofrizal, Nofrizal (Jurnal Daya Saing, 2024)
Technological developments provide rapid changes, especially in the realm of business. One of them is Shoppe which is a marketplace for online buying and selling transactions. Sellers can carry out various innovations and creativity with their products in the Shoppe, so that buyers can be interested and buy these products. Word-of-mouth that is electronic (E-WOM) is a characteristic that can change consumer decisions in consumer decisions. Shopee users among students at Lancang Kuning University of Business Economics are the subject of this study. Students at Lancang Kuning University studying business and economics made up the study's population. One hundred persons made up the sample. Purposive sampling was used in this investigation. Data that is both qualitative and quantitative, along with data collecting methods like surveys and interviews, are used. Using the SPSS software, basic linear regression is the analysis technique employed. Digital word-of-mouth possesses a beneficial impact judgments about purchases and a large favorable effect on consumer satisfaction, according to the outcomes of a straightforward test of linear regression. Electronic word-of-mouth is influenced by both consumer happiness and purchase decisions made simultaneously.